Cadmium Pollution in Soil of Rice Fields Around Lapindo Mud Using The Geoaccumulation Index (I-Geo) - Listin Fitrianah; Sindi Nur Fadilah (Universitas Islam Raden Rahmat, Malang, 2025)
The Lapindo Mud Disaster is a phenomenon of overflowing mud from the earth's crust that occurred in Sidoarjo. One of the impacts of the hot mud eruption on agricultural fields. This study aims to analyze the content of heavy metal cadmium in the soil of rice fields around the Lapindo Mud. The heavy metals analyzed include Cadmium (Cd), which is used in the Geoaccumulation Index (Igeo), with Class 7 of Igeo used to determine the level of heavy metal contamination due to a disaster that occurs. The results of this study indicate the largest Cadmium (Cd) metal content in the sample in Gempol Sari village, at 1.08 mg / L and 0.007 mg/L, respectively. This exceeds the threshold set by the Environment Protection Ministry of China (EPMC) and contaminates the rice field environment. Based on the Igeo calculation (geoaccumulation index) applied to the concentration of heavy metals in rice field soil not contaminated by Cadmium, with an index value of 0 <igeo <1. Geoaccumulation Index figures in the research area, cadmium (Cd) content is within the normal range, so it is not included in the group of heavy metals that pollute the soil.